Exogenous catalase improves the goat seminal attributes at refrigeration temperature - SINGH, PALLAVI; RANJAN, R; KHARCHE, S D; SINGH, M K (The Indian Journal of Animal Sciences, 2020)
The objective of the present study was to evaluate the potential benefit of catalase (CAT) on sperm functional parameters (motility, viability, membrane integrity and acrosomal integrity) during liquid storage of buck spermatozoa at 0 h, 24 h, 48 h, 72 h and 96 h. Semen samples from bucks were pooled to avoid individual effect and diluted with tris-egg yolk-fructose extender with catalase (0 U/ mL (control), 200 U/mL, 400 U/ mL, 600 U/ mL and 800 U/ mL) at a final concentration of 400 million/mL. No significant difference was observed between treatments at 24 h with respect to motility, viability and plasma membrane integrity. However, acrosome integrity of control was significantly higher as compared to other concentrations. Motility, viability, plasma membrane and acrosome integrity were observed significantly highest for CAT @ 600 U/mL in comparison to other concentrations at 48 h, 72 h and 96 h of liquid storage at refrigeration temperature. The seminal parameters declined with the progression of storage time and remained over 50% even after 72 h at refrigeration temperature in CAT @ 600 U/mL. It can be concluded that the addition of CAT @ 600 U/mL in semen diluent along with 20% egg yolk reduced the detrimental effects of cooling on motility, viability, plasma membrane and acrosome integrity.